Computer modelling reveals new conformers of the ATP binding loop of Na+/K+-ATPase involved in the transphosphorylation process of the sodium pump - Tejral, Gracian; Sopko, Bruno; Necas, Alois; Schoner, Wilhelm; Amler, Evzen (PeerJ, 2017)
Hydrolysis of ATP by Na+/K+-ATPase, a P-Type ATPase, catalyzing active Na+ and K+ transport through cellular membranes leads transiently to a phosphorylation of its catalytical α-subunit. Surprisingly, three-dimensional molecular structure analysis of P-type ATPases reveals that binding of ATP to the N-domain connected by a hinge to the P-domain is much too far away from the Asp369 to allow the transfer of ATP's terminal phosphate to its aspartyl-phosphorylation site. In order to get information for how the transfer of the γ-phosphate group of ATP to the Asp369 is achieved, analogous molecular modeling of the M4-M5 loop of ATPase was performed using the crystal data of Na+/K+-ATPase of different species. Analogous molecular modeling of the cytoplasmic loop between Thr338 and Ile760 of the α2-subunit of Na+/K+-ATPase and the analysis of distances between the ATP binding site and phosphorylation site revealed the existence of two ATP binding sites in the open conformation; the first one close to Phe475 in the N-domain, the other one close to Asp369 in the P-domain. However, binding of Mg2+•ATP to any of these sites in the "open conformation" may not lead to phosphorylation of Asp369. Additional conformations of the cytoplasmic loop were found wobbling between "open conformation" <==> "semi-open conformation <==> "closed conformation" in the absence of 2Mg2+•ATP. The cytoplasmic loop's conformational change to the "semi-open conformation"-characterized by a hydrogen bond between Arg543 and Asp611-triggers by binding of 2Mg2+•ATP to a single ATP site and conversion to the "closed conformation" the phosphorylation of Asp369 in the P-domain, and hence the start of Na+/K+-activated ATP hydrolysis.
Keywords: Hinge movement; Open and closed conformations; M4M5 loop; Na+/K+-ATPase phosphorylation